Absorption, scattering, and refractive index of blood and its components: a review - Gennadi Saiko; Faraz Sadrzadeh-Afsharazar; Timothy Burton; Scott Prahl; Alexandre Douplik; Alexandre Douplik (Frontiers in Photonics)
Blood is a complex biofluid with distinct optical characteristics that underpin a range of diagnostic and monitoring technologies. This review examines the absorption, scattering, and refractive index properties of whole blood and its components across the visible and near-infrared spectrum. Blood’s optical properties are determined primarily by water, hemoglobin, and its encapsulation in red blood cells. Hemoglobins dominate blood’s light absorption in the 400–1,100 nm range, with sharp spectral differences between oxygenated and deoxygenated forms. Scattering in whole blood is primarily due to red blood cells and is influenced by hematocrit, oxygenation, shear rate, and osmolarity. Reduced scattering coefficients are close to 13 cm−1 in the whole visible range of the spectrum, and the anisotropy factor is close to unity, indicating highly forward-directed scattering. While other blood cells (white blood cells and platelets) do not contribute significantly to blood’s optical properties, their scattering properties are used in many biomedical applications. We also highlight the role of the geometry of experiment—including detour, sieve, and self-shielding phenomena—in shaping blood’s optical response. Multiple clinical technologies, such as pulse oximetry, are based on blood’s optical properties. Recently reported discrepancies between consumer and clinical devices highlight the need for more accurate models of blood optics for emerging biomedical and wearable sensing applications.